Translation and Cognitive Structures - Schmied, Josef (HERMES - Journal of Language and Communication in Business, 2017)
This project is based on a corpus of English and German source and target texts, ranging from contemporary literature to scientific textbooks. We try to create a machine-readable and aligned corpus which will allow us to discover and categorize translation equivalents for a number of linguistic items, such as prepositions, subordination, deictic elements, metaphors or culture-specific structures. On this basis we look for regularities in the configuration of factors that influence equivalent choices for each of the phenomena in question. Apart from theoretical insights into contrastive language structures as well as cognitive aspects of the translation process, the purpose of the project is to discover and categorize prototye and non-prototype equivalents in two closely related languages. Research results could, for instance, be applied to bilingual lexicography or other language learning and translation aids.